Upaya Meningkatkan Kosakata Pada Anak Tunarungu - Aprizia Perenial Asla Wahyudi; Farah Aziizah; Reighina Faridah Solihah; Tiara Dwi Putri NSP; Siti Hamidah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research focuses on efforts to improve vocabulary in deaf children by conducting an in-depth literature review. Through a systematic literature review method, this research reviews various techniques that have been implemented and recorded in the academic literature on vocabulary education for deaf children. The data sources are journal articles from 2019 to 2024, which discuss teaching methods and technology applications including the use of visual aids, sign language, and hearing support devices. The purpose of this study was to assess the effectiveness of various existing methods and recommend the most effective techniques based on empirical data. The results of the review showed that the integration of visual, interactive and context-based methods often provided substantial improvements in vocabulary acquisition in deaf children. Based on these results, the study makes recommendations for teaching practices as well as future research directions.